ANALYSIS OF IMPLEMENTATION OF CHARACTER EDUCATION IN LEARNING DURING COVID-19 PANDEMIC ERA (CASE STUDY IN SD NEGERI 2 KARANGSARI) - Natasa, Anggit Putri; Suryandari, Kartika Chrysti; Suhartono, Suhartono (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
AbstractThe study aimed to describe the implementation of character education in SD Negeri 2 Karangsari during the Covid-19 Pandemic Era. It used a qualitative method with a case study approach. Data collection techniques were questionnaire, observation, interviews and documents. Data analysis was based on Miles and Huberman theory included data reduction, data presentation, and verification. The results showed that the character education was integrated in learning process. The nationalist character became habit, the religious character were developing, while the character of independence, integrity, and mutual cooperation began to grow. The characters of students at SD Negeri 2 Karangsari were influenced by internal and external factors. The obstacles in implementing characters to students were: (1) controlling the students was very difficult, (2) the students lacked of motivation, (3) the students had limited time of online learning, (4) the school lacked of learning facilities and learning media. The solutions were: (1) the teacher cooperated with parents, school committees and educational institutions, (2) the teacher motivated students, (3) the teacher integrated character values in learning materials, and (4) the teacher participated in workshop to create innovative learning media. It concludes that the implementation of education at SD Negeri 2 Karangsari during the Covid-19 Pandemic Era works well.